2021
DOI: 10.4102/phcfm.v13i1.2997
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of disease complications and risk factor monitoring amongst diabetes and hypertension patients attending chronic disease management programmes in a South African Township

Abstract: Background: South Africa established chronic disease management programmes (CDMPs) called ‘clubs’ to ensure quality diabetes care. However, the effectiveness of these clubs remains unclear in terms of disease risk factor monitoring and complication prevention.Aim: We assessed risk factor monitoring, prevalence and determinants of diabetes related complications amongst type-2 diabetes (T2D) and hypertension (HTN) patients attending two CDMPs.Setting: Urban Township in Cape Town, South Africa.Methods: Cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A narrative study also suggested poor glycemic control across SSA countries due to poor knowledge of T2D in patients [36]. Evidence has also reported inadequate monitoring of disease-related complications regardless of chronic care programmes in place, hence stressing the importance of incorporating self-monitoring strategies to reduce T2D-related complications [37]. Despite differences in study methods (study design, parameters of comparison and sample size), there is a clear indication of poor glycemic control across primary care facilities in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…A narrative study also suggested poor glycemic control across SSA countries due to poor knowledge of T2D in patients [36]. Evidence has also reported inadequate monitoring of disease-related complications regardless of chronic care programmes in place, hence stressing the importance of incorporating self-monitoring strategies to reduce T2D-related complications [37]. Despite differences in study methods (study design, parameters of comparison and sample size), there is a clear indication of poor glycemic control across primary care facilities in Africa.…”
Section: Discussionmentioning
confidence: 99%